2022
DOI: 10.1021/acs.accounts.1c00648
|View full text |Cite
|
Sign up to set email alerts
|

Visualizing the Multistep Process of Protein Aggregation in Live Cells

Abstract: Conspectus Protein aggregation is a biological phenomenon in which aberrantly processed or mutant proteins misfold and assemble into a variety of insoluble aggregates. Decades of studies have delineated the structure, interaction, and activity of proteins in either their natively folded structures or insoluble aggregates such as amyloid fibrils. However, a variety of intermediate species exist between these two extreme states in the protein folding landscape. Herein, we collectively term these intermediate spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 55 publications
0
25
0
Order By: Relevance
“…For more than 40 years, scientists have characterized the effects of the cellular interior on protein function. The advances in technology, such as in-cell NMR [ 9 , 99 ], single-cell mass spectrometry [ 100 ], fluorescence [ 8 , 10 , 101 , 102 ], FRET [ 103 ] and flow cytometry [ 104 ], electron microscopy [ 5 , 6 , 7 ], and cryo-electron tomography (Cryo-ET), allow scientists to characterize the protein and the protein aggregate structure and function in cells. Cryo-ET is particularly effective at structural characterization of the neurotoxic aggregates [ 105 , 106 , 107 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For more than 40 years, scientists have characterized the effects of the cellular interior on protein function. The advances in technology, such as in-cell NMR [ 9 , 99 ], single-cell mass spectrometry [ 100 ], fluorescence [ 8 , 10 , 101 , 102 ], FRET [ 103 ] and flow cytometry [ 104 ], electron microscopy [ 5 , 6 , 7 ], and cryo-electron tomography (Cryo-ET), allow scientists to characterize the protein and the protein aggregate structure and function in cells. Cryo-ET is particularly effective at structural characterization of the neurotoxic aggregates [ 105 , 106 , 107 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the cells and extracellular matrices, the proteins fold and misfold in a crowded environment, surrounded by a complex (and nonrandom) mixture of other solutes [ 3 , 4 ]. Ideally, fibrillation would primarily be studied in living organisms [ 5 , 6 , 7 , 8 , 9 , 10 ], however, measuring the kinetics of fibrillation in the cells poses obvious technical challenges. Instead, researchers have attempted to mimic the crowded environment of cells in vitro, via crowding agents [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…10,11 To explore mechanistic details of protein misfolding and aggregation, Liu [12][13][14] and our group [15][16][17] developed a series of fluorogenic tools based on fluorescence activation. These probes respond to changes in both polarity and viscosity during protein aggregation (Figure 1A, left panel) [18][19][20] , which mostly featured properties based on viscosity sensitivity. Increased viscosity in the local microenvironment of the protein aggregate restricts the internal rotation of fluorophores, resulting in fluorescence enhancement (Figure 1A, left panel).…”
Section: Introductionmentioning
confidence: 99%
“…These probes respond to changes in both polarity and viscosity during protein aggregation (Fig. 1A, left panel), 18–20 which mostly featured properties based on viscosity sensitivity. Increased viscosity in the local microenvironment of the protein aggregate restricts the internal rotation of fluorophores, resulting in fluorescence enhancement (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Panels of different non-covalent probes and sensors have been designed to illuminate the complex misfolded and aggregated conformations, including unfolded proteins, misfolded oligomers, amyloid aggregates, and amorphous aggregates. Compared with the non-covalent probes targeting aggregated proteins, covalent probes were still underdeveloped due to the lack of chemical strategies to explore the reactivity inside the misfolded and aggregated proteins. Recently, the Hong and Hatters group first demonstrated that unfolded proteomes can be targeted by globally labeling the exposed cysteine residues via maleimide chemistry and AIEgens upon stress-induced proteome unfolding in live cells. , Echoing Hong’s discovery, our group revealed that cysteine thiols were generally activated upon protein aggregation and can be covalently labeled by 1,4-Michael addition using a color-switch probe .…”
Section: Introductionmentioning
confidence: 99%